2002
DOI: 10.1093/brain/awf178
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variants of autoimmune peripheral nerve hyperexcitability

Abstract: Clinicians use many terms including undulating myokymia, neuromyotonia, Isaacs' syndrome and Cramp-Fasciculation Syndrome to describe the motor manifestations of generalized peripheral nerve hyperexcitability (PNH). Our previous findings in a selected group of patients with undulating myokymia or neuromyotonia, and EMG doublet or multiplet ('myokymic') motor unit discharges, indicated that an autoantibody-mediated potassium channelopathy was likely to be the cause of their disorder. This prompted us to search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
287
3
18

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(319 citation statements)
references
References 28 publications
11
287
3
18
Order By: Relevance
“…Although no HLA association has yet been demonstrated, other autoimmune diseases are commonly present, and about 20% of patients have a thymoma which can predate the symptoms or be identified after presentation of the neurological disease. Some patients also have MG. [80] However, in contrast to MG and LEMS, some patients appear to have a monophasic illness that recovers spontaneously within a few months or years. There is circumstantial evidence that these forms of the disease occur following an infection or other immune response; one patient developed the disease after multiple wasp stings.…”
Section: Immunological Basismentioning
confidence: 99%
See 1 more Smart Citation
“…Although no HLA association has yet been demonstrated, other autoimmune diseases are commonly present, and about 20% of patients have a thymoma which can predate the symptoms or be identified after presentation of the neurological disease. Some patients also have MG. [80] However, in contrast to MG and LEMS, some patients appear to have a monophasic illness that recovers spontaneously within a few months or years. There is circumstantial evidence that these forms of the disease occur following an infection or other immune response; one patient developed the disease after multiple wasp stings.…”
Section: Immunological Basismentioning
confidence: 99%
“…[89] Central Nervous System Disease with Voltage-gated Potassium channel Antibodies Although the typical neuromyotonia patient does not have central symptoms, some have sensory nerve involvement and sleep problems or anxiety are not infrequent. [80] Some patients have severe neuromyotonia with additional autonomic and marked central symptoms. This is usually called Morvan's syndrome.…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…has been reported as a selective activator of SK2 and SK3 channels (Hougaard et al, 2007), and several selective small molecule channel blockers have been developed (Chen et al, 2000;Faber & Sah, 2002). Neuron hyper-excitability is an essential component of many disorders of the central nervous system (Curatolo et al, 2001), and also plays a role in the molecular basis of addiction (Koob & Le Moal, 2001) and autoimmune disorders (Hart et al, 2002). In particular, it produces enhanced pain transmission in the spinal dorsal horn after spinal cord injury (Gwak & Hulsebosch, 2011).…”
Section: Potential Host Receptors Of Na-asp-2mentioning
confidence: 99%
“…Discoveries of the pathological mechanisms underlying AChR-based forms of myasthenia helped to distinguish the pathological mechanisms causing other forms of myasthenia. For example, discovery that myasthenia gravis (MG) is caused by an antibody-mediated autoimmune response to muscle AChRs (Drachman, 1994;Lindstrom, 2000aLindstrom, , 2002a laid the conceptual and methodological groundwork for discoveries that: first, Lambert-Eaton myasthenic syndrome (LEMS) is caused by an antibody-mediated autoimmune response to presynaptic active zone voltage-gated calcium channels (Newsom-Davis, 1998;Lang and Vincent, 2002); second, that autoimmune myasthenia lacking antibodies to AChRs or calcium channels have autoantibodies to a receptor tyrosine kinase (Hoch et al, 2001); and, most recently, that autoantibodies to potassium channels can cause peripheral nerve hyperactivity syndromes (Hart et al, 2002). Similarly, studies of the genetic bases of congenital myasthenic syndromes (CMSs) have revealed not only more than 60 mutations in AChR subunits, but also mutations in the collagen tail of the muscle form of acetylcholinesterase, the muscle AChR binding protein rapsyn, choline acetyltransferase, plectin, and other synaptic proteins yet to be identified (Engel et al, 1999(Engel et al, , 2002a.…”
Section: Introductionmentioning
confidence: 99%